Study of techniques to increase the autonomy of electric cars - BIRANE MOHAMMED ELSADEK; A. MAHDJOUBI (Amar TELIDJI University-LAGHOUAT-Faculty of Technology -Electrotechnical department, 2025)
. In this work, we studied electric vehicles from several perspectives, focusing on innovation and renewal in this field. We addressed a set of modern ideas that have contributed, and continue to contribute, to the development of electric vehicle performance, whether in terms of battery capacity, user comfort, or response to environmental challenges. We addressed the general concepts related to electric vehicles, in terms of their basic components and operating mechanism. We also focused on technologies for increasing electric vehicle range and the factors affecting their efficiency by presenting these factors. We also simulated a battery management strategy using the Arduino system, focusing on monitoring the state of charge, distributing energy efficiently, and ensuring battery safety through an intelligent management system that contributes to improving the vehicle's overall performance.
Option: Electrotechnical industrial